Increasing levels of rapeseed expeller meal in diets for pigs: effects on protein and energy metabolism. (28th May 2018) - Pérez de Nanclares, M.; Marcussen, C.; Tauson, A.-H.; Hansen, J. Ø.; Kjos, N. P.; Mydland, L. T.; Bach Knudsen, K. E.; Øverland, M.
Abstract : The heavy reliance on imported soybean meal (SBM) as a protein source makes it necessary for the European pig industry to search for alternatives and to develop pigs that perform efficiently when fed such ingredients. Digestion and metabolism are major physiological processes contributing to variation in feed efficiency. Therefore, an experiment was conducted to assess the effects of replacing SBM with increasing levels of rapeseed meal (RSM) in diets for young pigs on apparent total tract digestibility (ATTD) of energy and nutrients, nitrogen (N) balance, energy metabolism and carbohydrate, protein and fat oxidation. Four diets were fed to 32 pigs (22.7±4.1 kg initial BW) for three weeks. The diets consisted of a control cereal grain-SBM basal diet and three test diets where SBM and wheat were partially replaced with 10%, 20%, and 30% of expeller RSM. Increasing level of RSM in the diets linearly reduced ATTD of organic matter, CP, total carbohydrates, dietary fiber and energy. Utilization of digested nitrogen (DN) for N retention and total N excretion were not affected by RSM inclusion, however, RSM inclusion induced a shift in N excretion from urine to feces. Despite a linear increase in liver to metabolic BW ratio, heat production and utilization of metabolizable energy (ME) for retention were not affected by increasing RSM inclusion. In conclusion, replacing SBM with up to 30% of expeller RSM in nutritionally balanced diets for young pigs reduced the ATTD of most nutrients and energy, but did not affect N and energy retention in the body or efficiency of utilization of DN or ME for retention.